Evaluation of selected aspects of the Nutrition Therapeutic Programme offered to HIV-positive women of child-bearing age in Western Cape Province, South Africa - Tine T. Hansen; Marietjie Herselman; Lisanne du Plessis; Luzette Daniels; Tirsa Bezuidenhout; Cora van Niekerk; Laura Truter; Per O. Iversen (AOSIS, 2015)
Background: The Nutrition Therapeutic Programme (NTP) involves the provision of food supplements at primary health clinics (PHCs) to correct nutritional deficiencies in vulnerable groups. Although previous studies have identified problems with implementing the programme at PHCs, assessments of its efficiency have been scarce. Objective: To evaluate implementation of the NTP at PHCs that provide antiretroviral therapy. Methods: A cross-sectional, descriptive study was conducted at 17 PHCs located within 3 districts of Western Cape Province. Two target groups were chosen: 32 staff members working at the sites and 21 women of child-bearing age enrolled in the NTP. Questionnaires were used to obtain data. Results: Only 2 women (10%) lived in food-secure households; the rest were either at risk of hunger (29%) or classified as hungry (61%). Most of the women knew they had to take the supplements to improve their nutritional status, but the majority only recalled receiving basic nutritional advice, and the information was mainly given verbally. Ten of the women had shared their supplements with others, mostly with their children. The study identified lack of clearly defined NTP responsibilities at the PHCs, causing confusion amongst the staff. Although many staff members expressed problems with the NTP, only 38% of them reported having routine evaluations regarding the programme. Conclusion: Several aspects compromised the effectiveness of the NTP, including socio- economic factors leading to clients' non-compliance. The strategic organisation and implementation of the NTP varied between different PHCs offering antiretroviral therapy, and staff experienced difficulties with the logistics of the programme.